Determinação do consumo, digestões totais, balanço dos compostos nitrogenados e variáveis ruminais em ovinos santa inês alimentados com diferentes níveis de concentrado - Carneiro, Hilton Alexandre Vidal (2011)
The experiment w as conducted at the Department of Animal Scie nce, Federal University of Cear a in order to evaluate the effect of four levels of concentr ate (25.0, 37.5, 50.0, 62.5 on DM basis) in the diet of sheep on intake, digestibility of total dry matter (DM), organic matter (OM), crude protein (CP), ether extract (EE), neutral detergent fiber (NDF), neutral detergent fiber corrected for ash and protein (NDF), acid detergent fiber (ADF), total carbohydrates (TC) and non - fiber carbohydrates (NFC ) rumen pH, rumen ammoni a concentrations (NAR), nitrogenous compounds (BN) and plasma urea nitrogen (PUN) . We used sixteen castrated male sheep of Santa Ines body weight of 26.4 kg ± 4.13 kg and approximately seven months old. The animals were housed in individual metabolic cages equipped with collectors and tabs of feces and urine, and mangers for the supply of food and water fountains with water continuously available. The experimental design was randomized blocks with four treatments and four replications, totaling 16 experimen tal plots. T he experimental period lasted 28 days with 21 days of adaptation and seven days to collect samples. The animals were fed diets containing Tifton 85 hay and concentrate (25.0, 37.5, 50.0 and 62.5% ), which consisted of four experimental treatment s. The diets were formulated according to NRC (2007) to meet the nutritiona l requirements of sheep 200g. day - 1 gain. Diets were fed to animals once a day (800h), in form of a total mixture. Daily consumption of dry matter was determined by the difference be tween the bid and the remains of food offered. Feed samples, orts and feces were daily weighed and sampled for chemical analysis subseqente. Feces were collected for seven consecutive days to estimate the digestibility of dietary nutrients. The DM, OM, TC and NDT in g /d were not affected (P> 0.05) by concentrate feed. Increasing linear behavior was observed for intakes of CP, and NFC. For the intake of NDF, NDF, ADF and these linearly decreased. For consumption expressed as% of BW, there was a linear increasing and decreasing for MS to NDF equal behavior was observed for DM intake expressed in (g / kg 0, 75 ). The digestibility 9 of DM, OM, CP, CT and NSC increased (P <0.05) with the level of dietary concentrate. Rumen pH showed a linear response for diets with lower levels of concentrate and a quadratic for the experimental treatment with high level of concentrate as a function of time post - prandial. The diet influenced the concentrations of NH3 - N in the rumen (NAR) decreased linearly to levels of 37.5 and 50% of the concentrate and a quadratic for the 62.5% level of inclusion of dietary concentrate. The concentrate levels did not influence the excretion of nitrogen (N) in faeces ( g /d ) and urine (g /d ). The NB was positive at all levels of concentrate . PUN values among diets, showing a quadratic behavior. The addition of dietary concentrate influences the consumption and digestibility of nutrients, ruminal and promotes retention of nitrogen in the animal's body.